Replicating state Quitline innovations to increase reach: findings from three states - Paula A. Keller; Rebecca K. Lien; Laura A. Beebe; Jane Parker; Paola Klein; Randi B. Lachter; Stephen Gillaspy (BMC, 2020)
Abstract Background Reaching tobacco users is a persistent challenge for quitlines. In 2014, ClearWay MinnesotaSM changed its quitline services and media campaign, and observed substantial increases in reach and strong quit outcomes. Oklahoma and Florida implemented the same changes in 2015 and 2016. We examined whether the strategies used in Minnesota could be replicated with similar results. Methods We conducted a cross-sectional observational study of Minnesota's QUITPLAN® Services, the Oklahoma Tobacco Helpline, and Florida's Quit Your Way program. Each program offers free quitline services to their state's residents. For each state, data were compared for 1 year prior to service changes to 1 year after services changed and promotions began. Registration and program utilization data from 21,918 (Minnesota); 64,584 (Oklahoma); and 141,209 (Florida) program enrollees were analyzed. Additionally, outcome study data from 1542 (Minnesota); 3377 (Oklahoma); and 3444 (Florida) program enrollees were analyzed. We examined treatment reach, satisfaction, 24-h quit attempts, 30-day point prevalence abstinence rates, select demographic characteristics, registration mode (post period only), and estimated number of quitters. Data were analyzed using χ2 analyses and t-tests. Results Treatment reach rates increased by 50.62% in Oklahoma, 66.88% in Florida, and 480.56% in Minnesota. Significant increases in the estimated number of quitters were seen, ranging from + 42.75% to + 435.90%. Statistically significant changes in other variables (satisfaction, 24-h quit attempts, 30-day point prevalence abstinence rates, gender, and race) varied by state. During the post period, participants' method of registration differed. Online enrollment percentages ranged from 19.44% (Oklahoma), to 54.34% (Florida), to 70.80% (Minnesota). In Oklahoma, 71.63% of participants enrolled by phone, while 40.71% of Florida participants and 26.98% of Minnesota participants enrolled by phone. Fax or electronic referrals comprised 8.92% (Oklahoma), 4.95% (Florida), and 2.22% (Minnesota) of program enrollees, respectively. Conclusions Changing quitline services and implementing a new media campaign increased treatment reach and the estimated number of participants who quit smoking in three states. Quitline funders and tobacco control program managers may wish to consider approaches such as these to increase quitline utilization and population health impact.